Progress of ketogenic diet in the treatment of developmental epileptic encephalopathy - Hu, Wandong; Li, Lili; Zhao, Fen; Zhang, Huan; Zhang, Hongwei (Frontiers in Pediatrics, 2025)
Developmental epileptic encephalopathy (DEE) is a severe neurological disorder caused by underlying genetic abnormalities and frequent epileptic activity. It is characterized by early-onset, drug-resistant epilepsy, abnormal electroencephalogram (EEG) findings, and developmental delay or regression. DEE is associated with high rates of disability and mortality. The ketogenic diet (KD) is a well-established non-pharmacological treatment for refractory epilepsy and has demonstrated therapeutic efficacy in several DEE subtypes. In certain cases, it may reduce or even eliminate the need for pharmacological interventions. This review discusses the current clinical application of KD in children with DEE and summarizes key factors influencing its therapeutic effectiveness.